THE PRACTICE AND OBSTACLE FACTORS IN THE TEACHING OF ENGLISH TO YOUNG LEARNERS IN PUBLIC PRIMARY SCHOOLS IN PRINGSEWU, LAMPUNG PROVINCE, INDONESIA - Nana Apriliana (Kajian Linguistik dan Sastra, 2018)
In learning English for beginners like children, teachers have a very important role and will have a big effect on the outcomes of the learning process. In fact, most students in primary schools are difficult to understand English. Therefore, this study is aimed to examine the practices and obstacle factors in the teaching of English to young learners in six public primary schools (grade 4-6) in Pringsewu, Lampung province. This is descriptive research study that observes the process of teaching and learning and gives interviews to the teachers related to the teaching of English to young learners to gather relevant and proper data. The data is analyzed  based on themes and categories identified from the available literature quantitatively and qualitatively. The findings indicate English is taught through Indonesian language. Moreover, it shows that teachers who teach English are lack of proper pre-service training because most of them are not graduated from English Education. Therefore, they are lacking understanding and knowledge of the purpose, procedures and approaches of teaching English to young learners. The teachers also lack of in-service professional development courses on how to deal with young learners because the English position is only as local content. English gets less attention from both schools and government. Therefore, they never get in-service training, textbooks, syllabus and other facilities. This study recommends the change of minister of education regulation that positioning English as a local content to be compulsory subject to maximize the learning process to meet the challenge of globalization era.